Breeding habitats of Aedes aegypti mosquitoes and awareness about prevention of dengue in urban Chidambaram: a cross sectional study - A. R., Boornema; T. K., Senthil . Murugan (International Journal Of Community Medicine And Public Health, 2018)
Background: Dengue is an acute viral infection with potential fatal complications. It can be controlled by effective vector control measures. The present study was carried out to identify preferred breeding habitats of the vector. Also the knowledge and awareness among people regarding dengue fever was assessed. Methods: This is a cross sectional study conducted for a period of one month. Lot quality technique was used to select five streets in urban area, Chidambaram. A pre tested proforma and questionnaire was used. Results: A total of 205 households was surveyed. The mean age of the study population was 43.38 years. 71.7% were females. 47.8% were qualified till college. 52.2% were housewives. 80% were aware that dengue was transmitted by mosquito bite. 31.7% of them knew that aedes mosquito spread the disease and 56.6% were aware that its a day biter. Most of the information was obtained through television (43.1%). 33.7% of them used mosquito repellents. 62% preferred seeking immediate medical care for fever during outbreaks. Numbers of indoor and outdoor breeding sites were 15 and 126 respectively. The refrigerator trays were the most common indoor breeding site (42.2%). Discarded plastic containers were the major outdoor breeding habitat. The association between knowledge about dengue with education and source of information was found to be statistically significant (p<0.05). Conclusions: Dengue is one of the major public health problem which can be effectively controlled with active participation of the community and also by implementing sustainable vector control measures.